(untitled) (Research in Agriculture Livestock and Fisheries, 2019)
The experiment was carried out at the research farm of Bangladesh Institute of Nuclear Agriculture, Mymensingh, Bangladesh during December 2015 to January 2016 to evaluate the effects of cow dung (CD), poultry manure (PM) and mustard oil cake (MOC) along with NPK fertilizer amendments on the growth and yield performances of red amaranth in silty loam soil. The treatments were (i) NPK (control), (ii) NPK + CD, (iii) NPK + PM and (iv) NPK + MOC. All three types of manures significantly increased the plant height and numbers of leaves plant-1, thereby fresh weight, yield compared with the control (NPK). The best results in terms of vegetable fresh yield were obtained in the following order: NPK > CD > PM > MOC. Application of MOC is not beneficial due to 30 times higher price than CD and PM. PM added NPK fertilizer combination showed higher vegetable yield (10.87 t ha-1) than CD added NPK fertilizer combination (10.17 t ha-1). PM added fertilizer combination also had almost equal investment and cost-benefit ratio in comparison with CD. The lowest marginal benefit-cost ratio (1.09) was observed in MOC added NPK fertilizer combination though it showed higher vegetable yield (11.08 t ha-1). The farmers’ can be recommended to follow NPK + CD fertilizer combination. Manures applied post soil analysis showed improves the soil physiochemical properties. Res. Agric., Livest. Fish.6(2): 263-269, August 2019